Democracia, estado e indústria em a nova política do Brasil - Viviani, Fabrícia Carla (2013)
The main objective of this research is to analyze the A Nova Política do Brasil a compilation of pronouncements of the Vargas First Government, between 1930-1945 , and the central themes that was broadly debated by the specialized literature of the period about the position of the Vargas First Government regarding politics, state and economy. For the first element, it is pointed out the discussions about democracy, liberalism and organicism. For the second, and related to the first, the questions of the state centralization and intervention, bringing up the idea of that state configuration. Finally, the last element, intermingled with the two firsts and separated only for analytical reasons , that evoke a discussion about the economic transformations occurred along that period, and expressed in the tensions of the agrarian vocation e industrial vocation debate. Struggle that had as result the industrial development inclination. Despite this dilemma had been pointed consensually by specialized literature, the comprehension of that process dynamics and solutions are dissensual, generating various interpretations about the theme. Thus, the proposal of this thesis is to understand the 1930-1945 period as a process in construction, moving the controversies to the idea of process, trying to get how this has occurred in the level of the relations between the actors involved. We choose focuses on state, for sake of its role of protagonist broadly recognize by the experts of the period. We aggregated to this discussion a closer look upon the Vargas first government too, taken here as a catalyst of the new pact of alliances that was forming along the period, whose definition resulted of disputes in political field. Thus, this makes plausible the analysis of discursive production of that government condensed in A Nova Política. For this intention, it was called upon to the Gramsci s ideas in relation to the process, structure and conjuncture and to Pocock and his suggestions about the interfaces between text and context.